Increase Cardiovascular Event in Patient with Diabetes Mellitus Undergoing Percutaneous Coronary Intervention - Millisani, Hayla Iqda; Prasetya, Indra; Rohman, Mohammad Saifur; Satrijo, Budi (Heart Science Journal, 2024)
Diabetes mellitus (DM) associated with increase major risk factors of cardiovascular disease, such as peripheral arteriopathy, ischemic heart disease, or cerebrovascular accident. The Framingham study showed that patient with DM considerably increase coronary artery disease (CAD), particularly in old patient and women. Prevalence of DM is rising and cardiovascular mortality associated with DM is the main problem in the world. Additionally, there is a higher death rate among DM patients following a myocardial infarction with complications, such as stent thrombosis, instent restenosis, and no reflow phenomenon can worse overall long term prognosis with CAD. This review c onsiders the mechanism for diabetes mellitus in CAD patient, expecially patient with DM can increase risk of major complication in patient CAD undergoing percutaneous coronary intervention (PCI).